Behavior of Salmonella Typhimurium on Fresh Strawberries Under Different Storage Temperatures and Wash Treatments - Wang, Wen; Zhou, Yu; Xiao, Xingning; Yang, Guiling; Wang, Qiang; Wei, Wei; Liu, Yuanjing; Yang, Hua (Frontiers in Microbiology, 2018)
Fresh strawberries are one of the most popular fruits in China and are vulnerable to microbial contamination. In this study, the behavior of Salmonella Typhimurium on fresh strawberries stored at refrigeration and room temperatures, as well as the effectiveness of mild heat wash treatments at 47, 50 and 53 ºC on bacterial survival was investigated. The modified Gompertz, Huang, log-linear and Weibull models were used to fit bacterial growth and survival curves under different treatments. A secondary model based on linear regression was developed to describe the effect of washing temperature on the kinetic parameters of S. Typhimurium survival derived from the Weibull model. During 72 hours storage, S. Typhimurium on fresh strawberries stored at 4ºC was reduced by 1.35 log CFU/g and growth of 5.64 log CFU/g was observed when strawberries were stored at 25ºC. Bacterial reductions of 1.22 ± 0.15, 1.92 ± 0.06, 2.27 ± 0.07 log CFU/g were obtained when washing was carried out at 47, 50 and 53°C for 240 s, respectively. The wash temperature was an important parameter for bacterial inactivation and bacterial populations declined significantly in conjunction with washing time (p < 0.05). Warm wash treatments lead the visible color changes of strawberries, showing a slightly darker appearance while acceptable. The goodness-of-fit indices indicated that the log-linear model provided a satisfactory fit to describe the bacterial survival at 4ºC. According to the smaller Akaike information criterion (AIC) value, the modified Gompertz model performed slightly better than the Huang model in describing bacterial growth at 25ºC. The high adj-R2 (≥ 0.90) and small RMSE (≤ 0.22) indicated the Weibull model better described bacterial behavior under mild heat treatments. We found a close linear relationship between wash temperatures and ln k and ln n. These models were validated by independent experimental data and the values of the bias and accuracy factors fell into the acceptable range.